The Doctrine of the Holy Spirit in the Confession of the Toraja Church and Its Implementation for the People of the Toraja Church Leppan Congregation - Salombe, Yafet Sapan; Prasetyo, Yosafat Gratia; Aulu, Ronald (Proskuneo: Journal of Theology, 2025)
Christians or churches generally believe and acknowledge that the Holy Spirit is one of the persons of the single Triune God, but in congregational life, the Holy Spirit is misunderstood and often there are various views about the  Holy Spirit personhood and how the Holy Spirit works in the lives of believers. . In fact, if we return to the church's confession which is formulated based on the scriptures, it is clearly stated that the Holy Spirit is a person. In the Toraja Church's confession, the Holy Spirit is specifically recognized as a Person, however in this confession the author observes that further emphasis or explanation of the Person of the Holy Spirit is still inadequate. So it is not surprising that there are still many members of the Toraja Church who do not understand or even misunderstand the Holy Spirit and the work of the Holy Spirit in everyday life, as in the case of one member of the Toraja Church, the Leppan Congregation, who claimed that he had encountered the Holy Spirit. Through a spiritual experience that he dared to claim to be a prophet and even dared to judge several members of the other congregation that they were unrighteous and controlled by Satan.  Therefore, in the author's opinion, the doctrine of the Holy Spirit still needs to be given further explanation and is very important to be emphasized in the lives of church members. This is important so that church members gain a correct understanding of the Holy Spirit as stated in the holy scriptures